Sosialisasi Pengolahan Sampah dan Ecobrick : Don’t Break Make Ecobrick di Dukuh Mantren - Astiana Ajeng Rahadini; Anggoro Adji Pangestu; Anisa Caroline; Annisa Nur Chasidiyah; Annisaa Diah Putri Kesdu; Dwi Safitri; Ivanka Fajar Maulana; Salma Siti Aisyah; Wulan Ayu Harya Dinatta; Zidan Nasywan Firdaus (PT PUSTAKA CENDEKIA GROUP, 2025)
Waste is one of the problems that has yet to be fully addressed. Lack of understanding about the importance of waste segregation and processing, as well as limited management facilities, especially for plastic waste, makes the people of Dukuh Mantren tend to process waste in an inappropriate way. Therefore, education about waste management is needed. The purpose of this work program is to find out the condition of integrated waste management in the community and what factors support and hinder integrated waste management in the Dukuh Mantren community. The data obtained is then used for alternative strategies that can be used in integrated waste management in the Dukuh Mantren community. This education program is carried out through socialization, observation, and interview methods. The results of the Waste Management and Ecobrick Socialization Program carried out by KKN Tematik UNS proved effective in overcoming waste problems in Dukuh Mantren, Klodran Village. The program succeeded in increasing the community's understanding of the types of waste and how to process them properly. This research confirms that the Waste Management and Ecobricking Socialization program has a positive impact on overcoming the waste problem in Dukuh Mantren, Klodran Village.